Diabetes and schizophrenia - Gough, S (2005)
At a time when the prevalence of type 2 diabetes is increasing at an alarming rate it is becoming clear that patients with severe mental illness including schizophrenia represent a high-risk group for abnormal glucose homeostasis. There is, therefore, a need to raise awareness of the link between diabetes and schizophrenia and provide clear advice and guidance to health care professionals involved in the management of these patients. Copyright © 2005 John Wiley and Sons, Ltd.